Challenging Western Dominance: Islamic Intellectual Paradigms of Education in al-Ghazali, Ibn Qayyim, and al-Zarnuji - Charles Charles; Ade Putra Hayat; Febria Sri Artika; Herdianto Herdianto (Jurnal Ushuluddin, 2025)
Modern educational systems frequently emphasize cognitive outcomes, often at the expense of moral and spiritual development, resulting in graduates who may be academically adept yet ethically or spiritually unfulfilled. This study aims to reconstruct a holistic educational paradigm inspired by the pedagogical philosophies of three Islamic intellectuals—Al-Ghazali, Ibn Qayyim Al-Jauziyah, and Az-Zarnuji—by examining their conceptualizations of purposive learning, moral cultivation, and the role of the educator. Using a qualitative literature review method, the research analyzes primary classical texts and compares their holistic framework with Western holistic educational traditions such as Waldorf and the Humboldtian model. The findings reveal a tripartite pedagogical structure: spiritual purification (tazkiyat al-nafs), ethical integrity as a safeguard against intellectual hubris, and etiquette-infused teacher–student dynamics. These elements, when synthesized with Western models that prioritize creativity, individuality, and interdisciplinary growth, offer a robust paradigm for integrated human development. Ultimately, this framework proposes an education reoriented toward cognitive, ethical, and spiritual wholeness